2016
DOI: 10.1159/000445899
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Executive Dysfunction in Children and Adolescents with Chiari Malformation Type 1

Abstract: Background: Children with Chiari malformation type 1 (CM1) have increasingly presented to neurosurgery clinics. Limited research relating to the cognitive dysfunction experienced by this population has been completed. In adults, inhibition problems and executive dysfunction have been documented. Methods: Seventy-seven parental reports of children with CM1 were included in the study. Parents completed questions on a scale rating daily executive functioning as well as reporting on common neurological symptoms. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
7
1
4
Order By: Relevance
“…CM is a condition that has received considerable attention with regard to structural and fluid mechanic characteristics associated with the diagnosis (Shaffer et al 2011; Luciano et al 2014; Houston et al in press), but much less emphasis has been given to the possible affective and cognitive sequelae (but see Allen et al 2014; Lacy et al 2016; Garcia et al unpublished observations). While Allen et al (2014) observed executive function deficits in CM patients after controlling for the effect of functional disability due to pain; the present study illustrates the impact that pain has on recall memory – and the potential moderating effects of reflection and surgical status.…”
Section: Discussionmentioning
confidence: 99%
“…CM is a condition that has received considerable attention with regard to structural and fluid mechanic characteristics associated with the diagnosis (Shaffer et al 2011; Luciano et al 2014; Houston et al in press), but much less emphasis has been given to the possible affective and cognitive sequelae (but see Allen et al 2014; Lacy et al 2016; Garcia et al unpublished observations). While Allen et al (2014) observed executive function deficits in CM patients after controlling for the effect of functional disability due to pain; the present study illustrates the impact that pain has on recall memory – and the potential moderating effects of reflection and surgical status.…”
Section: Discussionmentioning
confidence: 99%
“…En los niños también se puede detectar trastornos de conducta (Novegno et al, 2008). Cabe señalar, que los que tienen dolor de cabeza, dificultades para tragar y trastornos de la marcha como síntomas principales pueden tener mayor riesgo de deterioro cognitivo y desregulación emocional (Lacy et al, 2016).…”
Section: Resultsunclassified
“…No obstante, a pesar de la evidencia en las alteraciones cognitivas como la memoria (Tavano et al, 2007), funciones ejecutivas (Koziol y Barker, 2013) o alteraciones en el lenguaje (Fabbro et al, 2004) sólo cuatro artículos abordan las funciones cognitivas tras la intervención (Allen et al, 2014;Allen et al, 2017;Riva et al, 2011). Lacy et al (2016) indicaron que el funcionamiento ejecutivo informado por los padres no se vio afectada por la cirugía ni la depresión. En esta misma línea Allen et al (2017) no lograron identificar diferencias grupales generales en el rendimiento del recuerdo entre los sometidos a descomprensión de la fosa posterior y los no sometidos.…”
Section: Discussionunclassified
See 2 more Smart Citations